2016
DOI: 10.1111/and.12648
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin abrogates nonylphenol-induced testicular dysfunction in Wistar rats

Abstract: Endocrine-disrupting chemicals present in the environment can bring about hormonal imbalance and be potentially harmful to the human health. Alkylphenols are omnipresent in the environment as they are constituents of several products. The aim of this study was to evaluate the effect of exogenous melatonin treatment on nonylphenol (NP)-induced oxidative stress and testicular toxicity in Wistar rats using biochemical and histopathological parameters. The oxidative stress biomarkers, activities of enzymatic and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In consonance with previous study, melatonin acts as a free radical scavenger that eliminates reactive oxygen and promotes the action and expression of endogenous antioxidants [ 26 , 57 ]. Our results are also consistent with a number of studies who have demonstrated anti-inflammatory, anti-proliferative and apoptotic properties of melatonin in experimental animals [ 58 60 ]. Nevertheless, the present results are not without limitations in such that the molecular mechanisms underlying the regulatory role of melatonin in obese animals, and the link between obestatin and other biochemical parameters were not investigated.…”
Section: Discussionsupporting
confidence: 93%
“…In consonance with previous study, melatonin acts as a free radical scavenger that eliminates reactive oxygen and promotes the action and expression of endogenous antioxidants [ 26 , 57 ]. Our results are also consistent with a number of studies who have demonstrated anti-inflammatory, anti-proliferative and apoptotic properties of melatonin in experimental animals [ 58 60 ]. Nevertheless, the present results are not without limitations in such that the molecular mechanisms underlying the regulatory role of melatonin in obese animals, and the link between obestatin and other biochemical parameters were not investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, MLT has an excellent antioxidant property. Therefore, MLT can reduce the number of oxidative products such as hydroxyl, peroxyl radical, hypochlorous acid and singlet oxygen which cause cell damage (Tabassum, Parvez, & Raisuddin, ). The direct effects of MLT on male reproductive system have been investigated in animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Nonylphenol, an environmental contaminant, is known to have adverse effects on the mammalian reproductive system (Duan et al., 2016). NP deteriorative effects have been observed through disturbing testicular structure, spermatogenesis, reducing testis size and inducing oxidative stress (Tabassum et al., 2017). To the best of our knowledge, this study evaluated the effect of ALP extract on NP‐induced reproductive toxicity for the first time using nonenzymatic and enzymatic biomarkers of oxidative stress in the serum of male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that NP causes reproductive dysfunction and enhances the production of reactive oxygen species (ROS) in the testis, liver and brain of animals (Kazemi et al, 2018; Kazemi, Feizi, et al, 2016; Kazemi, Mousavi Kani, et al, 2016). It has been evident that NP could reduce testis size, decrease circulating testosterone, disturb the testicular structure and suppress spermatogenesis (Tabassum et al., 2017; Ying et al., 2012). NP exposure decreased the lumen's diameter and epithelial thickness of seminiferous tubules leading to testicular atrophy (Jager et al., 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation